Sediment Transport Dynamics in the Upper Nara Canal Off-taking from Sukkur Barrage of Indus River - Mahessar, A. A.; Qureshi, A. L.; Kori, S. M.; Faoowui, G. S.; Memon, N. A.; Memon, A. A.; Leghari, K. Q. (Engineering, Technology & Applied Science Research, 2020)
Sediment material transported by the Indus River has two origins, the catchment and its wetted perimeter, whereas the amount of materials transported from the river itself depends on variables such as the flow type and the sediment load. The annual sediment load transported in the Indus River ranged from 270 to 600 million tons (MT) before the building of dams and barrages. The average sediment load is 0.715 MT/day or approximately 260 MT/ year after the construction of hydraulic structures. The average particle size, D50, of the bedload is approximately 0.125mm at the Sukkur barrage [1]. In this study, research was conducted to evaluate sediment problems in the Nara Canal, take-off from the left pocket of the Sukkur Barrage on the Indus River. The collected data from the left pocket, the bed, and suspended material in upper Nara and its off-taking canals were analyzed to assess sediment transport dynamics of upper Nara canal at various locations and its off-taking canals. The bed material at RD 553+600 shows a minimum size of 0.07 and a maximum of 0.7mm with 54% fine-sand mixed with 46% medium-sand in 2003. Fine-sand increased to an average of 75% while medium sand diminished to 25% at RD 553+600 in Nara canal and at RD 595+000 in Jamrao complex in 2013. The suspended load with low and high flows during 2012 exhibits that in all the cases the sand proportion was increasing in the Upper Nara canal system flowing to the Jamrao complex. The sediment concentration value indicates that there is the deposition of sand at the upper Nara canal and the Jamrao complex causing a discharge reduction in the Nara Canal system.